Relation of microchannel identified by optical coherence tomography to clinical, angiography and other plaque morphological characteristics in ST-segment Elevation myocardial infarction patients. (25th November 2020) - Wang, J; Dai, J; Fang, C; Yu, B
Abstract: Background: Previous studies have suggested that Microchannel (MC) is associated with plaque progression and vulnerability. Optical coherence tomography (OCT) could provide a chance to directly visualize plaque neovascularization in vivo. Methods: 1268 STEMI patients who underwent OCT examination of culprit lesion were included and divided into MC group (the culprit plaque with MC, n=560) and no-MC group (the culprit plaque without MC, n=708). MC was defined as a no-signal tubuloluminal structure on the cross-sectional optical coherence tomographic image. Clinical, angiography and other plaque morphological characteristics were compared between the two groups. Logistic regression analysis was used to identify independent predictors of MC in overall. In addition, the difference of predictors on MC was found in plaque rupture (PR) and plaque erosion (PE). Results: Significant differences between MC group and no-MC group were found in the frequency of thin-cap fibroatheroma (74.6% vs 64.4%, p<0.001), lipid plaque (91.8% vs 82.9%, p<0.001), lipid core length (13.7±6.5mm vs 12.6±6.3mm, p=0.006) and the minimal lumen area (MLA, 1.95±0.98mm 2 vs 2.10±1.58mm 2, p=0.046). In MC group, the other vulnerable plaque morphological characteristics, such as macrophage (88.8% vs 75.1%, p<0.001), cholesterol crystal (39.6% vs 32.9%, p=0.013), spotty calcification (38.6% vs 29.5%, p<0.001) were more frequent. And compared with MLA the more locations of the culprit lesion in MC group was proximal (proximal, 47.3% vs 38.1%, at MLA, 38.2% vs 44.2%, distal, 14.5% vs 17.7%, p=0.004).The difference of Hemoglobin (Hb, 147.5±16.9g/L vs 144.1±18.2g/L, p<0.001), lipidemia (TC, 188.7±43.6mmol/L vs 180.8±40.0mmol/L, p<0.001, LDL-C, 121.5±37.4mmol/L vs 115.7±36.8mmol/L, p=0.005, and TC/HDL, 4.0±1.6 vs 3.8±1.0, p<0.001), and hypertension (50.7% vs 44.2%, p=0.021) between 2 groups was statistically significant. Multivariable logistic regression models showed 7 independent parameters associated with MC in culprit plaque of overall: hypertension, Hb, TC, MLA, lesion location (compared with MLA), lipid core length, macrophage, spotty calcification. In addition, Hb, TC and MLA were common predictors of MC in PR and PE, however, the predictive effect of MLA on MC was opposite in PR [OR (95% CI)=1.266 (1.095–1.463), p=0.001] and PE [OR (95% CI)=0.742 (0.597–0.922), p=0.007]. Conclusions: MC in culprit plaque is associated with more lipid (especially cholesterol), higher Hb, hypertension, lesion location (compared with MLA) and the other vulnerable plaque morphological characteristics. The predictors of MC were different in plaque rupture and plaque erosion. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Natural Science Foundation of China (81827806, 81801861); National Key R&D Program of China (2016YFC1301100)